(untitled) (DARYAFT, 2025)
Anees Ashfaq’s novel “Heech” reflects the shifting political and social conditions of Indian Muslims. It effectively portrays the identity crisis, fear and communal prejudice faced by minorities particularly Muslims. The novel highlights the ongoing religious discrimination, anti-Muslim sentiments and the rise of extremist political ideologies in contemporary India. The characters in “Heech” are caught in a struggle for survival and the preservation of their identity. Anees Ashfaq explores the complexities of human psychology, belief systems and political motives through a unique and symbolic narrative style. “Heech” is not merely a portrayal of Muslim victimhood but a profound social critique that exposes the contradictions within the current Indian system. Interestingly, the Hindu characters in the novel also express discontent with the prevailing circumstances, emphasizing that communal bias affects the entire society not just the minorities. Anees Ashfaq’s narrative technique and literary voice hold a distinctive place in Urdu literature. This study attempts to explore how the identity and security of the Muslim individual are represented in literary texts against the backdrop of contemporary Indian political discourse.